How e-filling system can improve taxpayer compliance in raising tax revenues - Purnamasari, Dyah (Opción, 2019)
This paper aims to determine the effect of e-filling system to improve taxpayer compliance and its implications in increasing tax revenues. This paper is a literature study using secondary data in the form of textbook theory and the results of previous studies. The result of research reveals that e-filling system improves taxpayer compliance that has an impact on increasing tax revenues. In conclusion, in order to improve taxpayer compliance, the Government should speed up the process of realization of good governance and the government regularly explains to the public regarding the allocation of the use of tax money.